PENGARUH EMPATHY CARE TRAINING TERHADAP PERILAKU ALTRUISME PADA RELAWAN COVID-19 DI DUSUN TRAJAYA KABUPATEN MAJALENGKA [THE EFFECT OF EMPATHY CARE TRAINING TOWARD ALTRUISM BEHAVIOR ON COVID-19 VOLUNTEERS IN TRAJAYA VILLAGE, MAJALENGKA REGENCY] - Ahmad Qomarudin Zain; Abdul Jafar (Perkumpulan Ahli Bimbingan Konseling Islam Indonesia, 2021)
This study aims to determine the effect of Empathy Care Training toward altruistic behavior in COVID-19 volunteers in Trajaya Village, Majalengka Regency. The design of this study used the pretest and posttest control group design. The research data collection used the altruism scale from Aviani (2019) and used the Likert scale. The research subjects were ten of COVID-19 volunteers in the village of Trajaya, Majalengka Regency who were divided into two groups of five people each for the experimental group and the control group. The data analysis method used the Wilcoxon and Mann Whitney U technique by testing the difference in gainscore in the control group and the experimental group. The results of the Mann Whitney U test analysis showed the value of Z = -1.781 and the value of p = 0.0375 (p <0.05) this indicated that there was a significant difference between the control group and the experimental group. The results showed that Empathy Care Training had an effect on altruism behavior in COVID-19 volunteers in the village of Trajaya, Majalengka Regency.